A new Cumulative Gravitational Search algorithm for optimal placement of FACT device to minimize system loss in the deregulated electrical power environment. (January 2017) - Packiasudha, M.; Suja, S.; Jerome, Jovitha
Graphical abstract: Highlights: Real time industrial zone that consists of wind power and solar power. The Southern Regional Load Dispatch Centre (SRLDC) 72 bus system. The results are verified by conventional method, modeled in Simulink and by algorithmic method. Abstract: The optimized position of placing FACT device in an industrial zone is a challenging task. If the FACT device is perfectly placed, the reactive power losses can be controlled within a limit and can improve the real power flow in the power system network. Many algorithms have been developed in the recent years using Swarm intelligence, Genetic algorithm, Honey Bee search and fish schooling algorithms. Gravitational search algorithm based on Newtonian law of gravity between masses is used to find the minimum value accurately. In Opposition based GSA (OGSA) instead of considering both active and passive masses, the passive mass alone is considered which is equivalent to reactive power force component. The active force is not considered. The resultant force obtained is less accurate. But in Cumulative Gravitational Search Algorithm (CGSA) active and passive mass interactions are together considered so the resultant force obtained between the masses will be effectively taken into account. Two different mass inertia, namely active mass and passive mass are applied in CGSA, and exact results can be found. In this algorithm, the search agents are a collection of masses which interacts with each other based on Newtonian gravity and laws of motion. In this research, 72 bus southern grid system and a 16 bus real time industrial zone are tested by conventional method, modeled using MATLAB/Simulink and by using the proposed CGSA. The optimized place to connect the FACT device is found and compared with conventional and modeling method.